Improving technical maintenance of systems of mini hydropower plants - analysis of causes of malfunctions, faults, failures and system failures - Žegarac, Nikola P. (Vojnotehnički glasnik / Military Technical Courier, 2017)
The paper presents many years of experience related to the activities of technical maintenance of mechanical and electrical plants. It shows the analysis of the cause of many malfunctions, faults, failures and system failures that occur in mini hydropower plants. Systems of mini hydropower plants are discussed in terms of improving the technical maintenance by functional units: turbine regulator with turbine, mechanical assemblies (multiplier and flywheel), flexible couplings that connect plant assemblies, electrical circuits, lubrication systems, automation and high-voltage installations. Below is a brief overview of the application possibilities of technical diagnostics i.e. of a monitoring system in mini hydropower plants.
Keywords: technical maintenance; mini hydropower plants; faults; malfunctions; system failures; bearings; flexible couplings; mechanical assemblies; electrical circuits